Mental fatigue impairs tackling technique in amateur rugby union players - Davidow, D.; Smith, M.; Ross, T.; James, G. L.; Paul, L.; Lambert, M.; Jones, B.; Hendricks, S. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To test the effects of mental fatigue (MF) on tackling technique on the dominant and nondominant shoulders in rugby union.